Pengembangan Aplikasi Penentuan Prioritas Kebutuhan Fungsional Perangkat Lunak Berdasarkan Kebutuhan Non-Fungsional - Dini Indah Nurul Rizki Pancawati Raharjo; Tri Astoto Kurniawan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software requirements can be defined as services that software must provide in order to support user achieving the goal of using the software. Software requirements are the basis in the software development process. In situation where the source and time are limited it is important to prioritize the requirements. Requirements prioritization shows which requirement should be implemented first and get more attention in the implementation process. A research by Umang Garg and Abhishek Singhal, a method to prioritize software requirements based on non-functional requirements is proposed. In this research, an application to prioritize software functional requirements is developed in order to help the process of requirements prioritization, the method used in this research is the one that proposed by Umang Garg and Abhishek Singhal. Requirement prioritization started with a pair-wise comparison between the non-functional requirements, and then a pairwise comparison between functional requirements with non-functional requirements, lastly the order of requirements' priority and the value of priority are obtained. The system is tested by unit testing on 3 methods of the system, integration testing, and 27 test cases on validation testing which give valid results.